2018
DOI: 10.1038/s41565-018-0105-3
|View full text |Cite
|
Sign up to set email alerts
|

An artificial molecular machine that builds an asymmetric catalyst

Abstract: Biomolecular machines perform types of complex molecular-level tasks that artificial molecular machines can aspire to. The ribosome, for example, translates information from the polymer track it traverses (messenger RNA) to the new polymer it constructs (a polypeptide) . The sequence and number of codons read determines the sequence and number of building blocks incorporated into the biomachine-synthesized polymer. However, neither control of sequence nor the transfer of length information from one polymer to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
62
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(63 citation statements)
references
References 32 publications
0
62
0
1
Order By: Relevance
“…Leigh et al described a molecular machine that moves a substrate between different activating sites. 31,32 Anderson et al reported the template-directed synthesis of a porphyrin nanoball. 33 Fujita et al prepared palladium metal complexes and used them as catalyst carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Leigh et al described a molecular machine that moves a substrate between different activating sites. 31,32 Anderson et al reported the template-directed synthesis of a porphyrin nanoball. 33 Fujita et al prepared palladium metal complexes and used them as catalyst carriers.…”
Section: Introductionmentioning
confidence: 99%
“…These proteins comprise a motor domain, capable of moving directionally along a track by consuming a fuel (ATP), and a docking domain capable of picking up or releasing appropriate cargos on command. The design and construction of artificial molecular machines that can actively transport molecular or ionic substrates along specific directions, or across membranes, is a fascinating goal for nanoscientists, and may disclose unconventional routes in catalysis, smart materials, energy conversion and storage, and medical therapy . Outstanding examples of molecular robots capable of transporting and sorting cargos have been developed by engineering DNA architectures .…”
Section: Transport Of Molecular Cargosmentioning
confidence: 99%
“…The latest addition to this conceptual journey in the molecular world can be found in this issue in a Letter by De Bo et al 1 . The authors have made a molecule that can synthesize a second molecule, which in turn assumes a characteristic conformation that can catalyse the formation of a third molecule.…”
mentioning
confidence: 92%